The Slovenian Language and Slovenian Identity in the Early and Mature Works of Florjan Lipuš - Borovnik, Silvija (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
Florjan Lipuš is a Slovenian writer, a Carinthian Slovenian living in Sele, Austria, who writes exclusively in Slovenian. He entered the world of literature very early in life, while still a student and protégé at the secondary school in Plešivec, Tanzenberg, where he lived at the local boarding school with others preparing for priesthood. They secretly edited and published the student journal Kres in Slovenian. The fact that Lipuš’s mother tongue was unwelcome in Austria and that its use was virtually prohibited was something he had to face at an early age. This provoked such a rebellion in him that he later wrote all his literary works in Slovenian. As a mature writer, he added that this was the language of his mother, who, being a devout Slovenian, died in a German concentration camp and left